Count Loss Evaluation for Accuracy Enhancement of a FPGA-Based Gamma Spectroscopy - Hoai-Phuong Pham; Viet-Huy Le; The-Dat Trang; Nhi-Dien Nguyen (Science and Technology of Nuclear Installations)
The count loss, caused by the pileup event and the minimum time required for pulse processing, is necessarily evaluated to restore the counting information in quantitative analysis. In this work, a simple approach was proposed for evaluation of count loss due to the pileup event in gamma spectroscopy. A real-time digital multichannel analyzer based on a field-programmable gate array was commissioned subsequently to the detector’s preamplifier, and its performance is comparable to a commercial gamma spectroscopy. To identify the pileup event, a window whose timing equivalent to the trapezoid shaping time was employed. The number of count loss was modelled as the percentage of rejected pulse (PRP), whereas a pileup event is considered as two pulses. Experiment shows that the PRP is linearly proportional to the input rate and dependent on the shaping time. The PRP was proven reproducible with a statistical uncertainty of below 3%. The deterioration of a detected low-energy peak area induced by a high-energy radioactive source was realized experimentally, and the count loss evaluation was carried out. The results indicated that the approach in this study is superior to the live-time correction mode of the commercial system. The developed spectroscopy has been used in the designed measuring system for determining the activity and activity distribution of gamma-emitting isotopes in radioactive waste drums using the tomography gamma scanning (TGS) technique at the Dalat Research Reactor.